Options for reforming the devolved fiscal frameworks post-pandemic - David Bell; David Eiser; David Phillips (Institute for Fiscal Studies (IFS), 2021)
The COVID-19 pandemic has been a significant challenge for all tiers of government across the world. In the UK, the devolved governments of Northern Ireland, Scotland and Wales are responsible for most of the public services significantly impacted by the pandemic, and have designed and implemented large parts of the public health response to it. They have also been responsible for designing and administering grants and property tax reliefs for businesses. They have had to discharge these responsibilities and manage their budgets in the context of fiscal frameworks agreed before the pandemic - although the UK government made modest, but important, temporary changes to funding arrangements in 2020-21. These changes, in combination with the enormous increases in funding made available by the UK government, and the fairly symmetric impact of the pandemic across the four nations of the UK, meant the risk of a major funding crisis for the devolved governments was averted. But this 'success' does not mean there is not room for improvement to the existing fiscal frameworks in order to make them more robust to future shocks, or that the same ad hoc changes would necessarily be appropriate if another extreme adverse shock occurred. This report considers a range of options to reform the existing fiscal frameworks, with two main objectives in mind: first, to make them more robust to future crises, including a potential reintensification of the COVID-19 pandemic during Winter 2021-22; and second, to help the devolved governments support economic and social recovery from the pandemic.
Keywords: 330